Supplementation with β-carotene aids minimize inflammation in monosodium urate crystal- induced gouty arthritis in Wistar albino rats - Lavinya B Udhaya; Aline Ubrewe Rutera; K Ram Kumar; N Sangeetha; P Manisha; Sabina Evan Prince (Universidade de São Paulo, 2022)
Abstract Gout is a form of metabolic arthritis originated on grounds of increased accumulation of monosodium urate (MSU) crystals in joints. Current study focuses on anti-arthritic activities of β-carotene on MSU crystal-induced gouty arthritis rats in comparison with the non-steroidal anti-inflammatory drug, indomethacin. The evaluation was done by taking into account paw oedema, lysosomal enzymes, anti-oxidant enzymes, lipid peroxidation, serum biochemical parameters (uric acid, creatinine), serum cytokines (TNF-α, IL-1β) and histopathological studies. After the induction of MSU crystals, the lysosomal enzymes were increased, antioxidant enzymes were reduced, lipid peroxidation increased and paw volume increased. β-carotene treated at a dose of 10 mg/kg of body weight stabilizes lysosomal enzymes, increases anti-oxidant enzymes, regulates lipid peroxidation and decreased paw volume. The drug β-carotene potentially influences anti-inflammatory effects in arthritic group which is evident from the reduction in the elevated levels of inflammatory cytokines, TNF-α and IL-1β. Current study is an evidence of anti-inflammatory and anti-oxidant effects of β-carotene against MSU-crystal induced gouty arthritis rats.